Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3847/1538-3881/aaf0fb
|View full text |Cite
|
Sign up to set email alerts
|

The Eclipsing δ Scuti Star EPIC 245932119

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…From iterative pre-whitening pipeline we obtained 25 significant frequencies, 11 of which can be explained as harmonics or combination frequencies. We note that seven of the frequencies reported by Lee et al (2019) are either harmonics of the orbital frequency, or can be explained as second-order combination frequencies with the orbital frequency. Finally, 12 of the 25 frequencies in the TESS light curve of HD 220687 are above the Kepler/K2 long-cadence Nyquist frequency of 24.49 d −1 which emphasizes the usefulness of short-cadence observations for studying δ Sct stars.…”
Section: Tic 49677785 = Hd 220687mentioning
confidence: 71%
See 2 more Smart Citations
“…From iterative pre-whitening pipeline we obtained 25 significant frequencies, 11 of which can be explained as harmonics or combination frequencies. We note that seven of the frequencies reported by Lee et al (2019) are either harmonics of the orbital frequency, or can be explained as second-order combination frequencies with the orbital frequency. Finally, 12 of the 25 frequencies in the TESS light curve of HD 220687 are above the Kepler/K2 long-cadence Nyquist frequency of 24.49 d −1 which emphasizes the usefulness of short-cadence observations for studying δ Sct stars.…”
Section: Tic 49677785 = Hd 220687mentioning
confidence: 71%
“…Recently, HD 220687 was observed for approximately 80 d by the K2 mission (Howell et al 2014). From these K2 data and estimates of the primary's surface gravity and effective temperature from RAVE spectroscopy, Lee, Hong & Kristiansen (2019) obtained a binary model with the Wilson Devinney Code, albeit without an estimate for the mass ratio from radial velocities. After subtracting their binary light-curve solution, Lee et al (2019) found 35 significant frequencies with an S/N ≥ 4 using a noise window of the size 5 d −1 centred around each peak; all of these frequencies were inferred to be δ Sct pulsations.…”
Section: Tic 49677785 = Hd 220687mentioning
confidence: 99%
See 1 more Smart Citation
“…The LcTools community currently consists of 77 registered users worldwide. A recent survey of the publications posted on arXiv 1 found 20 papers that either cited or acknowledged use of the product for investigating various astronomical phenomena (C ¸okluk et al 2019;Gaidos et al 2019;Rappaport et al 2019a;Eisner et al 2019;Rappaport et al 2019b;Ansdell et al 2019;Borkovits et al 2019;Lee et al 2019;Oláh et al 2018;Rodriguez et al 2018;Borkovits et al 2018;Malavolta et al 2018;LaCourse & Jacobs 2018;Rappaport et al 2018;Zhou et al 2018;Christiansen et al 2018;Rappaport et al 2017;Schmitt et al 2016;Ansdell et al 2016;Kipping et al 2015). This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the strong synergy between EBs and pulsators can play a critical reciprocal role in providing significant information on the stellar parameters and internal structures. We have been searching for and characterizing the pulsating EBs using Kepler photometry (Lee et al 2014(Lee et al , 2019 and ground-based spectroscopy (Hong et al 2015;Lee & Park 2018). In this paper, our program target is TIC 309658221 (HD 34954, TYC 8878-116-1, GSC 8878-0116, 2MASS J05170089-6130524; V T = +10.31, (B − V ) T = +0.35; Høg et al 2000), which was known as a single F-type star prior to the TESS observations (Stassun et al 2018).…”
Section: Introductionmentioning
confidence: 99%